2000
DOI: 10.1097/00000542-200004000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Prophylactic Antiemetic Therapy with Ondansetron, Droperidol, or Placebo

Abstract: The use of prophylactic antiemetic therapy in high-risk ambulatory surgical patients was more effective in preventing PONV and achieved greater patient satisfaction at a lower cost compared with placebo. The use of 1.25 mg droperidol intravenously was associated with greater effectiveness, lower costs, and similar patient satisfaction compared with 0.625 mg droperidol intravenously and 4 mg ondansetron intravenously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1
22

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(170 citation statements)
references
References 2 publications
6
141
1
22
Order By: Relevance
“…The cost of treating vomiting was three times more than the cost of treating nausea. 59 Similar results were reported in another study where both droperidol and dolasetron were more cost-effective than no prophylaxis in high-risk patients. 133 In two separate cost-effectiveness analyses, Tang et al and Hill et al reported that droperidol was more cost-effective than ondansetron for PONV prophylaxis.…”
Section: Combination Antiemetic Therapy and Multimodal Approachsupporting
confidence: 85%
See 2 more Smart Citations
“…The cost of treating vomiting was three times more than the cost of treating nausea. 59 Similar results were reported in another study where both droperidol and dolasetron were more cost-effective than no prophylaxis in high-risk patients. 133 In two separate cost-effectiveness analyses, Tang et al and Hill et al reported that droperidol was more cost-effective than ondansetron for PONV prophylaxis.…”
Section: Combination Antiemetic Therapy and Multimodal Approachsupporting
confidence: 85%
“…In a dose of 1.25 mg, it was more cost-effective than ondansetron 4 mg and was recommended as a first line agent for PONV prophylaxis (IA). 59 The NNT to prevent early nausea was 5. For both early and late vomiting, the best efficacy was with 1.5 to 2.5 mg (NNT = 7).…”
Section: Older Generation Antiemeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os escores preditivos de Apfel são fáceis de aplicar, apresentando uma razoável preditibilidade sobre NVPO, e simultaneamente permitem a comparação entre vários grupos no domínio da investigação clinica de antieméticos. Alguns autores criticaram Apfel pela dificuldade de aplicar alguns dos seus fatores de risco 20 22 . Na conferência de consenso de 2003 foi recomendada profilaxia a pacientes com risco moderado a elevado para NVPO ou para aqueles com potencial morbidade associada a NVPO, especificamente deiscência de suturas, rotura esofágica, formação de hematoma e pneumonia aspirativa 21 .…”
Section: Identificação De Fatores De Risco Para Nvpounclassified
“…Additionally, persistent nausea and vomiting can delay discharge from hospital (1,2). Breast surgery is associated with a high (40% to 70%) incidence of PONV (3,4).…”
Section: La Dexaméthasone Intraveineuse Permet-elle De Prévenir Les Nmentioning
confidence: 99%